Mapping of Mobile Learning Research Directions and Trends in Scopus-Indexed Journals: A Bibliometric Analysis - Turmuzi, Muhammad; Suharta, I Gusti Putu; Astawa, I Wayan Puja; Suparta, I Nengah (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Compared to traditional classroom lessons, mobile learning is hailed as a simple, convenient, engaging, innovative, and modern means of learning. Students exhibit more self-discipline and organization during the mobile learning process. Mobile learning is becoming increasingly prevalent in the classroom. It is crucial to develop a shared understanding of the research conducted to comprehend how mobile learning is used. The goal of the study is to summarize the literature on mobile learning based on a bibliometric evaluation of several journal articles published in the Scopus database and to determine fresh ideas and knowledge gaps as a resource for more research. The technique is a bibliometric analysis using the programs VOSviewer, SEforRA, and Publish or Perish. The findings of this analysis show that from 2000 to 2018, the growth of mobile learning research on the Scopus database trended upward and peaked. The expanding trend of research on mobile learning has led to the discovery of numerous themes or keywords that might be used as the basis for further study. In conclusion, the bibliometric analysis provides knowledge and information about the development of mobile learning research for the possibility of a new study